Privatization of University Hospital And Its Impact on Improving The Quality of Health Services - Huda Muhammad Al-Abdul Rahman (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This research investigates the privatization of university hospitals and its impact on health service quality. It aims to understand how shifting from public to private management affects healthcare delivery, focusing on operational efficiency, patient care, accessibility, and medical service standards. The study synthesizes literature to assess privatization’s diverse effects, analyzing both its positive outcomes, like efficiency and patient care innovation, and challenges such as healthcare access equity and quality maintenance. The theoretical framework combines market efficiency, healthcare equity, stakeholder theory, and public goods theory, providing a comprehensive view of privatization. The methodology involves a descriptive and analytical review of various privatization models, identifying key themes and research gaps, especially the need for detailed studies on privatization’s long-term impacts and demographic effects. The discussion interprets these findings, noting the complexity of privatization’s effects. While it can enhance operational aspects, issues like equitable care access and quality maintenance are significant. The research concludes by summarizing these findings, suggesting future research areas, including longitudinal studies, and recommending policies and management strategies to align privatization with public health goals. This study offers insights for healthcare policy, management, and stakeholders, contributing to healthcare management discourse.